2009
DOI: 10.1186/1471-2350-10-34
|View full text |Cite
|
Sign up to set email alerts
|

The first Dutch SDHB founder deletion in paraganglioma – pheochromocytoma patients

Abstract: Background: Germline mutations of the tumor suppressor genes SDHB, SDHC and SDHD play a major role in hereditary paraganglioma and pheochromocytoma. These three genes encode subunits of succinate dehydrogenase (SDH), the mitochondrial tricarboxylic acid cycle enzyme and complex II component of the electron transport chain. The majority of variants of the SDH genes are missense and nonsense mutations. To date few large deletions of the SDH genes have been described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Deletion analysis of SDHD and SDHC by MLPA detected four deletions in a point mutation-negative group of 126 patients, so deletions of these genes represent 3% of all mutations identified. We have described a founder deletion of exon 3 of the SDHB gene in nine patients of this same group of point mutation-negative patients (Bayley et al 2009). While founder mutations are common in the Dutch population , Zeegers et al 2004, as once again shown by the identification of the SDHB exon 3 deletion, other populations also show founder effects (Cascon et al 2008, Peczkowska et al 2008b, Opocher et al 2009), indicating that while the general frequency of SDH deletions across all paraganglioma patient populations cannot yet be established, the proportion of deletions found in the Dutch population may have wider relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion analysis of SDHD and SDHC by MLPA detected four deletions in a point mutation-negative group of 126 patients, so deletions of these genes represent 3% of all mutations identified. We have described a founder deletion of exon 3 of the SDHB gene in nine patients of this same group of point mutation-negative patients (Bayley et al 2009). While founder mutations are common in the Dutch population , Zeegers et al 2004, as once again shown by the identification of the SDHB exon 3 deletion, other populations also show founder effects (Cascon et al 2008, Peczkowska et al 2008b, Opocher et al 2009), indicating that while the general frequency of SDH deletions across all paraganglioma patient populations cannot yet be established, the proportion of deletions found in the Dutch population may have wider relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Another patient (patient 4) showed J-P Bayley et al: Deletions of SDHD and SDHC www.endocrinology-journals.org deletion of SDHC exons 5 and 6. A founder deletion of exon 3 of the SDHB gene was identified in nine patients and has been described elsewhere (Bayley et al 2009). When all 13 patients with SDHB, SDHC, or SDHD deletions are taken in to account, deletions (13/138) represented w10% of all mutations identified in index patients, indicating that deletions can represent a significant proportion of all mutations in paraganglioma (PGL) patient groups (Table 1).…”
Section: Mlpa Analysismentioning
confidence: 99%
“…while the majority of patients undergoing SDHB mutation analysis have missense and nonsense mutations, some mutation negative patients have been reported to carry either large partial or total deletions of the SDHB gene [10][11][12][13][14][15][16][17][18]. to investigate this possibility, we carried out MLPA and identified a heterozygous SDHB gene deletion encompassing sequences corresponding to the promoter region, exon 1 and exon 2 ( Fig.…”
Section: Sdhb Mutation Analysismentioning
confidence: 99%
“…Given that only a small number of SDHB deletion cases have been described [10][11][12][13][14][15][16][17][18], it is difficult to meaningfully compare the phenotypes and penegest to us that these tests capable of detecting such large deletions, such as MLPA, should be made routine. Conceivably, MLPA could be used to screen for large deletions in all three SDHx genes in a single test.…”
Section: Mlpa Analysis [22]mentioning
confidence: 99%
See 1 more Smart Citation